A pair of noncompeting neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model. Issue 5 (13th September 2021) - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian R.; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Mueller‐Schmucker, Sandra; Habenicht, Katharina; Eberlein, Valentina; Issmail, Leila; et al.
Abstract: TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS‐CoV‐2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS‐CoV‐2 spike protein. Nine antibodies neutralize SARS‐CoV‐2 infection at IC50 values in the subnanomolar range. ELISA‐binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor‐binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N ‐terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS‐CoV‐2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS‐CoV‐2‐induced weight loss. The two clusters of potent noncompeting SARS‐CoV‐2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID‐19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives. Abstract : Transgenic mice with a complete human antibody repertoire (Trianni platform) were immunized with the spike protein (S protein) of SARS‐CoV‐2 and hybridoma clones were established. Two clusters of clonally related SARS‐CoV‐2‐neutralizing monoclonal antibodies were isolated. Cluster 1 binds to the N ‐terminal domain (NTD) and Cluster 2 to the receptor‐binding domain (RBD) of the CoV‐2 spike protein. The antibodies also significantly reduce the viral spread in hACE2‐transgenic mice.